Effects of diclofenac on the pharmacokinetics of celastrol in rats and its transport - Zengfu Wang; Dali Chen; Zhongwei Wang (Taylor & Francis Group, 2018)
Context: Diclofenac and celastrol are always used together for the treatment of rheumatoid arthritis; the herb-drug interaction potential between diclofenac and celastrol is still unknown. Objective: This study investigates the effects of diclofenac on the pharmacokinetics of celastrol in rats. Materials and methods: Twelve male Sprague-Dawley rats were divided into two groups and received celastrol (1 mg/kg) or both celastrol (1 mg/kg) and diclofenac (10 mg/kg) by oral gavage, and blood samples were collected via the oculi chorioideae vein and determined using the LC-MS method developed in this study. Additionally, the effects of diclofenac on the transport of celastrol were investigated using a Caco-2 cell transwell model. Results: Diclofenac could significantly (p < 0.05) decrease the Cmax (from 66.93 ± 10.28 to 41.25 ± 8.06 ng/mL) and AUC0-t (from 765.84 ± 163.61 to 451.33 ± 110.88 μg × h/L) of celastrol in rats. The efflux ratio of celastrol increased significantly (p < 0.05) from 3.12 to 4.55 with the treatment of diclofenac. Discussion and conclusion: These results indicated that diclofenac could decrease the system exposure of celastrol in rats when they are co-administered, and these effects might be exerted via decreasing its absorption in intestine.